EVALUASI TINGKAT KEBISINGAN TERHADAP KENYAMANAN BELAJAR PADA RUANG KELAS XII IPS 2 SMA LABORATORIUM UNIVERSITAS NEGERI MALANG - Fais Achmad Muzaki; Muhammad Aris Ichwanto; Meisya Sastyaviena Irawan; Isabella Rafi Anjani; Hartini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to evaluate acoustic performance based on noise levels and their impact on learning comfort in the XII IPS 2 classroom at SMA Laboratory, Universitas Negeri Malang. The research employed a descriptive quantitative approach using direct observation by measuring noise levels with a Sound Level Meter. Data collection was conducted from 10:00 to 12:00 during classroom activities. The results indicate that noise levels ranged from 51.65 to 56.03 dB, with an average of 53.28 dB. Compared to the Indonesian National Standard (SNI 03-6386-2000), which recommends 35–40 dB for classrooms, the measured values exceed the acceptable comfort level. However, the noise level remains below the environmental noise threshold of 55 dB based on the Decree of the Minister of Environment No. 48 of 1996. The elevated noise levels are influenced by both external and internal factors. Therefore, improvements such as the use of sound-absorbing materials and better management of building openings are necessary to enhance learning comfort.